Utilization of Empty Palm Fruit Bunches as a Carbon Source for Cellulase Production to Reduce Solid Waste from Palm Oil - Amraini, Said Zul; Nazaris, Nazsha Nayyazsha; Andrio, David; Mardhiansyah, Muhammad; Helwani, Zuchra (Leuser Journal of Environmental Studies, 2023)
Cellulase enzymes are widely used in textile, food, detergent, pulp and paper industries and biofuel, so the need for enzymes continues to increase every year. One of many biomass wastes found in Indonesia is empty fruit bunches (EFB) that can be used as a carbon source as a substitute for expensive pure cellulose (CMC) and Bacillus subtilis isolates. This study aims to obtain the optimum conditions the production of cellulase enzymes with variations in the pre-treatment of EFB and pH variations of the medium using Bacillus subtilis. Pre-treatment was carried out to hydrolysed lignocellulosic biomass was more easily and increased glucose levels which would enter the next production stage. Variations in pre-treatment were carried out by adding acids, bases and organosolv process, as well as variations in pH at 6.5; 7.0 and 7.5, respectively. Enzyme activity was calculated using the Nelson-Somogyi method. When using acid, the enzyme activity is 0.041, while using organosolv, it is obtained 0.057 each at pH 7. The results showed that the highest enzyme activity was obtained at a pH of 7.0 and a temperature of 40 ºC on EFB substrate pretreated with a base of 0.204 U/ml. These findings emphasize the potential benefits of using EFB waste as a substrate for cellulase enzyme production, by providing an alternative approach to decrease raw material expenses and mitigate environmental pollution.